A state-of-the-art review of road tunnel subjected to blast loads - Cheng, R.; Chen, Wensu; Hao, Hong; Li, Jingde (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Road tunnels are critical components in road transportation networks. In their service life they may subject to explosion loads from terrorist bombing attacks, engineering blasting for construction and accidental explosions from transported flammable goods. These extreme loading conditions might not only lead to catastrophic damages to tunnel structures, severe casualties and economic losses, but also have immeasurable social impacts. Therefore, it is imperative for engineers, researchers and policy regulators to understand the performance of road tunnels under explosion loads towards a reliable blast-resistant design of tunnel structures. This paper presents a state-of-the-art review of dynamic response, damage assessment and damage mitigation of tunnels under blast loads. The common road tunnels, various explosion scenarios, and the corresponding blast wave characteristics are reviewed first. Then the dynamic response and damage characteristics of tunnel structures under blast loads including the analysis methods of tunnel response, types of tunnel response and key factors influencing tunnel response are reviewed and discussed. The assessment criteria of tunnel damage and the damage mitigation measures for tunnels against blast loads are also reviewed. Finally, concluding remarks and several key research areas for future work are presented.